Evaluation of the oxidative stress alleviation in Lupinus albus var. orden Dorado by the inoculation of four plant growth-promoting bacteria and their mixtures in mercury-polluted soils - González-Reguero, Daniel; Robas-Mora, Marina; Probanza, Agustín; Jiménez, Pedro A. (Frontiers in Microbiology, 2022)
Mercury (Hg) pollution is a serious environmental and public health problem. Hg has the ability of biomagnifing through the trophic chain and generating various pathologies in humans. The exposure of plants to Hg affects normal plant growth and its stress levels, producing oxidative cell damage. Root inoculation with plant growth promoting bacteria (PGPB) can help reduce the absorption of Hg, minimizing the harmful effects of this metal in the plant. This study evaluates the phytoprotective capacity of four bacterial strains selected for their PGPB capabilities, quantified by the calculation of the biomercuroremediator suitability index (IIBMR), and their consortia, in the Lupinus albus var. orden Dorado. The oxidative stress modulating capacity in the inoculated plant was analyzed by measuring the activity of the enzymes catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR). In turn, the phytoprotective capacity of these PGPBs against the bioaccumulation of Hg was studied in plants grown in substrates highly contaminated by Hg versus soils in the absence of Hg contamination. The results of the phytoprotective capacity are compared with the biometric data of Lupinus albus var. orden Dorado previously obtained under the same soil conditions of Hg concentration. The results show that the biological behavior of plants (biometrics, bioaccumulation of Hg and activity of regulatory enzymes of reactive oxygen species (ROS)) is significantly improved by the inoculation of strains B1 (Pseudomonas moraviensis) and B2 (Pseudomonas baetica) as well as their corresponding consortium (CS5). In the light of the conclusions of this work, the use of these strains, as well as their consortium, is postulated as good candidates for their subsequent use in phytostimulation and phytoprotection processes in areas contaminated with Hg.